Comparative evaluation of crude preparation of Azadirachta indica leaf and Albendazole(R) in naturally infected goats with internal parasites - Dawo, F.; Asseye, Z.; Tibbo, Markos (2001)
A total of 55 goats were divided into 7 treatment groups of 7-8 goats. Five groups received different doses of the crude preparation of A. indica leaf: 0.5, 1.0, 2.0, 5.0 and 10.0 g/kg body weight. The other two groups were a negative control group (untreated) and a positive control group (treated with 7.5 mg/kg albendazole). Neither the crude preparation of the leaf of A. indica or albendazole were effective for the control of Trichuris.